2018
DOI: 10.1080/10584609.2018.1542416
|View full text |Cite|
|
Sign up to set email alerts
|

The (In)stability of Voters’ Perceptions of Competence and Associative Issue Ownership: The Role of Media Campaign Coverage

Abstract: This is a post-peer-review, pre-copy-edited version of the following article: Anke Tresch & Alexandra Feddersen (2018). The (in)stability of voters' perceptions of competence and associate issue ownership: The role of media coverage. Political

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…Further, work about the changeability of issue ownership over time has suggested that associative ownership is less changeable than competence ownership. That associative issue ownership is more invariant than competence ownership has been showed both in longitudinal (Tresch and Feddersen 2017;Walgrave and Lefevere 2017) and in experimental research (Tresch, Lefevere, and Walgrave 2015). This as well, and not only the fact that competence and association (or commitment) are two analytically different things, may affect our findings.…”
Section: Sources Of Associative Issue Ownershipmentioning
confidence: 49%
See 1 more Smart Citation
“…Further, work about the changeability of issue ownership over time has suggested that associative ownership is less changeable than competence ownership. That associative issue ownership is more invariant than competence ownership has been showed both in longitudinal (Tresch and Feddersen 2017;Walgrave and Lefevere 2017) and in experimental research (Tresch, Lefevere, and Walgrave 2015). This as well, and not only the fact that competence and association (or commitment) are two analytically different things, may affect our findings.…”
Section: Sources Of Associative Issue Ownershipmentioning
confidence: 49%
“…As good as all this work looks into competence issue ownership. Only two studies (Walgrave and Lefevere 2017;Tresch and Feddersen 2017) look at associative issue ownership as the dependent variable, but they too find an effect of party preference. Still, there are reasons to expect that party preference has a relatively smaller effect on associative compared to competence issue ownership perceptions.…”
Section: Sources Of Associative Issue Ownershipmentioning
confidence: 99%
“…The results suggest that key issues of an election campaign—that is, the masculine issue of immigration in the case of the federal elections in 2015—set the media’s issue agenda irrespective of candidates’ gender. Immigration policy has traditionally been “owned” by the Swiss People’s Party from the political right (Tresch and Feddersen 2019). The increased issue coverage for parties of the political right thus supports the notion that the media tend to respect these ownership patterns and report accordingly (Hänggli and Kriesi 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Second, and unlike the well-studied two-party system of U.S. politics, the Swiss party landscape is diverse with nine major parties occupying a wide range of ideological positions (Bochsler et al 2015). Party ideology is also linked to the “ownership” of political issues (Hänggli and Kriesi 2010; Tresch and Feddersen 2019), which, in turn, may help as a heuristic for political journalists. Third, incumbent and well-known politicians have been shown to benefit from greater media visibility in the Swiss media (Gilardi and Wüest 2017; Tresch 2009).…”
Section: Gender Context and Bias In Election Coveragementioning
confidence: 99%
“…Furthermore, while the early literature emphasized the stability of issue ownership (Petrocik, 1996), the recent literature has highlighted the possibility of short-term changes in voters' assessments of parties' issue competence. Looking at the sources of changes, some scholars find that party communication and media coverage lead to short-term shifts in voters' competence perceptions (Aalberg and Jenssen, 2007;Dahlberg and Martinsson, 2015;Tresch and Feddersen, 2018;Walgrave et al, 2009). Others delve into the consequences of these changes for electoral choice formation.…”
Section: Dynamics In Cumulative Issue Ownership As a Predictor Of Parmentioning
confidence: 99%